Relationship between vegetation and phisiography in a perpendicular transection to Azul brook (province of Buenos Aires) (Semiárida, 2020)
The northen area of the district of Azul (centre of the province of Buenos Aires) has mainly an alluvial plain landscape with natural grassland which are used to grow cattle. In order to study the relationship vegetation-environment in that landscape, the phyisiography and plant communities along a transversal transection to dominant geoforms were described. Six physiografic environments were identified on the basis of topographic survey photointerpretation and analysis of soils an topographic maps. In each environment the vegetation was studied by means of the phytosociologic method defining 19 floristic groups and 6 communities. The relative participation of the communities within each environment wasconditioned by predominant geoforms and microrelief features.
Keywords: plant communities; alluvial plain; phisiographic environments